Room-temperature photochemical preparation method of nano tungsten-copper composite material

Nanocopper particles are formed in the copper deposited solution through room temperature photochemical reaction and deposited in the gap between the tungsten powder layer, which solves the problem of poor stability of nanotungsten copper composites under high temperature treatment, and realizes the effect of preparing dense nanotungsten copper composites at room temperature .

CN119121200AActive Publication Date: 2024-12-13BEIJING UNIV OF TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411231748.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-13
Estimated Expiration
2044-09-04

AI Technical Summary

Technical Problem

The prior art requires high temperature process when preparing nanotungsten copper composite materials, resulting in poor thermal stability of nanocrystals and prone to instability, affecting material performance and structural uniformity.

Method used

Nano-tungsten copper composite material is prepared in one step by room temperature photochemical reaction. Nano-copper particles are formed under ultraviolet light irradiation through copper salts, sodium ascorbate and amino-containing additives in the copper deposited liquid, and deposited in the gap of the tungsten powder layer to form a dense structure. , avoid high temperature treatment.

Benefits of technology

The nanoscale dense tungsten copper composite material is prepared at room temperature, maintaining the stability and performance of the material, and avoiding the abnormal growth of grains and uneven phase distribution caused by high-temperature treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121200A_ABST
    Figure CN119121200A_ABST
Patent Text Reader

Abstract

The invention discloses a room-temperature photochemical preparation method of a nano tungsten-copper composite material, and belongs to the field of composite materials. Copper ions and sodium ascorbate form a photosensitive reduction system, and primary copper nanoparticles are generated under ultraviolet irradiation. Amino groups in the auxiliary agent form polydentate coordination for copper nanoparticles, each amino-containing auxiliary agent molecular chain can anchor a plurality of nanoparticles, and entanglement of different amino-containing auxiliary agent molecular chains enables the nanoparticles to form a spatial network. And an amide unit in the amino-containing auxiliary agent is used for adjusting the distance between amino groups, so that a proper distance is maintained between the nano-particles. Through the two effects, the primary nano-particles can continue to grow and be connected under continuous illumination, and a compact structure is formed. In addition, the tungsten nanoparticles can be wrapped by the long molecular chain of the amino-containing auxiliary agent, the problem that the tungsten-copper interface bonding is weak is solved, and copper generated by the photochemical reaction can be spread and deposited on the tungsten surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a nano-tungsten copper composite material in one step at room temperature by utilizing a photochemical reaction. The invention belongs to the field of composite materials. Background Art

[0002] Tungsten copper composite materials have high hardness, high strength, low thermal expansion coefficient, good arc resistance and excellent electrical and thermal conductivity. They are widely used in national defense, aerospace and civil industries, especially high-voltage circuit contact parts, welding electrodes, electronic packaging and heat dissipation devices. Due to the huge difference in the physical and chemical properties between tungsten and copper, the tungsten phase and the copper phase in the tungsten copper composite material cannot be effectively dissolved in each other, which hinders their interface bonding and densification, and limits the continuous high performance of tungsten copper composite materials. Recent studies have shown that the use of tungsten and copper nanoparticles as starting materials to prepare tungsten copper composite materials with nanoscale grain structure can effectively improve their comprehensive performance. This is because nanopowders have higher specific surface area and surface energy, and the interface bonding is more complete during sintering, and they tend to be more dense. At the same time, the rearrangement process of nano W particles during liquid phase sintering can provide higher capillary forces and accelerate the densification of tungsten copper composite materials. Nanoscale W and Cu particles also help to improve the microstructural uniformity of the material, thereby significantly improving its physical properties and mechanical properties.

[0003] At present, there are two main methods for preparing nano-tungsten copper composite materials. Based on the powder metallurgy infiltration method, a W skeleton with open nanopores can be prepared by dealloying, and then the molten Cu enters the W skeleton through capillary action and fills its gaps to form a nano-tungsten copper composite material. Based on the liquid phase sintering method, high-energy ball milling can be used to repeatedly deform and crush the raw materials, so as to achieve mechanical alloying of submicron mixing between elements, and then obtain nano-tungsten copper composite materials by cold pressing and sintering. In view of the fact that Cu is prone to cold welding and uneven distribution during the mechanical alloying process, mechanical-chemical alloying technology can be used to mix the raw materials. This method first mechanically grinds the oxides of W and Cu, uses the brittleness of metal oxides to obtain smaller and more uniform nano-mixed powders, and then obtains metal W and Cu by chemical reduction. In addition, wet chemical methods can also prepare nano-tungsten copper composite powders with good dispersibility. The precursor solution is sprayed, gelled or precipitated, and then calcined and reduced to convert the metal ions in the solution into metal nanoparticles.

[0004] Unfortunately, the above methods all require high temperature processes (usually >950°C) during preparation. Nanocrystals have poor thermal stability and are very easy to grow unstable under heating conditions, causing the product structure, composition, and phase distribution to deviate from the original design. For example, during the liquid phase sintering process, nano W particles can quickly grow to micron size, losing the nanoscale effect on product performance improvement; at the same time, due to the abnormal growth of grains at higher temperatures, it is easy to cause uneven distribution of the final product phase and grain size, affecting the physical and mechanical properties of the material. Therefore, it is urgent to develop new methods that can take into account both the nano-sizing of the grain structure of tungsten copper materials and the maintenance of stability, and break through the bottleneck of existing technologies. Summary of the invention

[0005] The present invention proposes a new method for obtaining nano-tungsten copper composite materials in one step by photochemical reaction at room temperature, thereby completely avoiding the high temperature process at the preparation mechanism level and solving the contradictions of the prior art. The specific implementation process of the present invention is as follows:

[0006] (1) Prepare copper deposition solution: Mix copper salt, amine-containing auxiliary agent and sodium ascorbate to prepare copper deposition solution. The copper salt can be copper chloride or copper sulfate, and its concentration range is generally between 10mM and 60mM; the concentration of sodium ascorbate is generally between 50mM and 200mM; after the amine-containing auxiliary agent is added, the amine concentration is controlled to be between 25mM and 140mM.

[0007] The amine-containing additive can be prepared as follows. Dissolve pentaethylenehexamine (PEHA) and acrylamide (AAm) in water to form a mixed solution, wherein the molar ratio of pentaethylenehexamine to acrylamide is controlled between 1:12 and 1:24, and the absolute concentration of pentaethylenehexamine is not less than 100mM. Add 10% ammonium persulfate or potassium persulfate solution by mass to the mixed solution. The volume of the ammonium persulfate or potassium persulfate solution is 5-10% of the total liquid. Let it stand for one day to allow the polymerization reaction in the solution to fully occur, and finally dilute it with water to make the amine concentration in the product uniform to 0.5M.

[0008] (2) Deposition preparation: Spread the nano-tungsten powder evenly on the substrate into a thin layer, the thickness of which generally does not exceed 10 μm. Add the copper deposition liquid to the substrate, the copper deposition liquid should cover the nano-tungsten powder, and the thickness of the deposition liquid surface to the substrate surface should be at least 400 μm ( Figure 1 ).

[0009] (3) Photochemical deposition: A 365nm ultraviolet light source is used to vertically irradiate the deposition liquid and the tungsten powder layer. The irradiation intensity on the sample surface is not less than 100mM / cm 2. Continue irradiation for 5-20 minutes to fully reduce the Cu ions in the deposition solution and deposit them in the gaps between the W powders to form a nano-W-Cu composite material. If a large amount of Cu is required, the deposition solution can be replaced after one deposition and multiple depositions can be performed. If a thicker WCu composite material is required, the sample can be washed with deionized water after Cu deposition, and then another layer of W powder can be applied. Repeat the above process until a satisfactory thickness ( Figure 2 ).

[0010] (4) In the above step (3), the spatially selective preparation of nano-tungsten copper composite materials can also be carried out. By focusing ultraviolet light on a specific position of the tungsten powder layer through a projection device, copper can be selectively deposited there. The surrounding unilluminated areas do not react. After the deposition is completed, the tungsten powder layer can be rinsed with a large amount of deionized water to wash away the unreacted part, leaving only the nano-tungsten copper composite material with copper deposited in the specific area. In this way, a nano-tungsten copper composite material of a certain shape can be prepared.

[0011] The room temperature photochemical preparation principle of nano-tungsten copper composite materials is as follows ( Figure 3 ):

[0012] Copper ions and sodium ascorbate form a photosensitivity reduction system, which produces primary copper nanoparticles under ultraviolet light. The amine groups in the additive form multidentate coordination with the copper nanoparticles. Each amine-containing additive molecular chain can anchor multiple nanoparticles. The entanglement of different amine-containing additive molecular chains forms a spatial network between the nanoparticles. The amide units in the amine-containing additive are used to adjust the amine spacing so that the nanoparticles maintain an appropriate distance. The above two effects allow the primary nanoparticles to continue to grow and connect under continuous light to form a dense structure. The long molecular chains of the amine-containing additive can also wrap around the tungsten nanoparticles, solving the problem of weak tungsten-copper interface bonding, so that the copper produced by the photochemical reaction can spread and deposit on the tungsten surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 Preparation for depositing copper in a tungsten powder layer.

[0014] Figure 2 Schematic diagram of the preparation of nano-tungsten-copper composite materials by photochemical deposition under different modes.

[0015] Figure 3 Schematic diagram of the working principle of the amine-based additive in the preparation of nano-tungsten-copper composite materials by photochemical deposition.

[0016] Figure 4Microscopic characterization of the nano-tungsten-copper composite material prepared in Example 1. (A) Microscope dark field image of W powder thin layer; (B) Microscope dark field image of W powder thin layer after Cu deposition; (C) Microscope dark field image of commercial tungsten-copper sample; (D) SEM image of the prepared nano-tungsten-copper composite material; (E) W element distribution in the area of ​​(D); (F) Cu element distribution in the area of ​​(D).

[0017] Figure 5 Effect of multiple depositions on Cu morphology in Example 2. (A) SEM photo of the sample surface after multiple depositions; (B) W element distribution in the area in (A); (C) Cu element distribution in the area in (A).

[0018] Figure 6 Effect of multi-layer deposition on sample thickness in Example 3. (A) Port morphology of a 4-layer deposited sample; (B) Port morphology of a 6-layer deposited sample.

[0019] Figure 7 The regional selective Cu deposition process in Example 4.

[0020] Figure 8 Limitations of using small molecule amine to assist copper deposition in Comparative Example 1. (A) Dark field micrograph of the deposited sample surface; (B) SEM lens of the deposited sample surface.

[0021] Fig. 9 Limitations of using a non-optimized amine-containing additive to assist copper deposition in Comparative Example 2. (A) Dark field micrograph of the deposited sample surface; (B) SEM images of the deposited sample surface. DETAILED DESCRIPTION

[0022] The present invention is further described below in conjunction with the following examples, but the present invention is not limited to the following examples. The light source in the following examples all adopts a 365nm ultraviolet light source.

[0023] Embodiment 1:

[0024] 0.3873g PEHA and 2.1324g AAm were dissolved in 16.5mL water to form a mixed solution, 1mL of 10% ammonium persulfate solution was added to the mixed solution, and the mixture was allowed to stand for one day. An auxiliary solution with an amine concentration of 0.5M was obtained, named P3A. Copper chloride, P3A, and sodium ascorbate were mixed to prepare a copper deposition solution. Among them, the concentration of copper chloride was 20mM, the concentration of amine was 30mM, and the concentration of sodium ascorbate was 100mM.

[0025] The substrate covered with a 200nm thin layer of tungsten nanoparticles was immersed in the deposition solution. The thickness of the liquid layer was maintained at 1mm and the irradiation intensity on the sample surface was 500mM / cm 2, irradiated for 10 minutes. Photochemical deposition was performed twice by replacing the deposition liquid. Optical microscopy of the sample showed that the red Cu phase filled the gaps between the W particles after deposition. Comparison with the commercial tungsten copper samples prepared by powder metallurgy showed that both had similar interpenetrating network structures, but the W and Cu phases in the composite material prepared by the present invention were nanoscale, and the organization was significantly finer than that of the commercial tungsten copper samples. Scanning electron microscopy confirmed that the W and Cu particles in the composite material prepared by the present invention formed an interpenetrating and relatively dense continuous structure, and the particle size was maintained in the range of 100-200nm. The density obtained by image analysis was >99.7% ( Figure 4 ).

[0026] Embodiment 2:

[0027] Copper chloride, P3A, and sodium ascorbate were mixed to prepare a copper deposition solution. The concentration of copper chloride was 20 mM, the concentration of amine was 30 mM, and the concentration of sodium ascorbate was 100 mM. A substrate covered with a thin layer of 200 nm tungsten nanoparticles was immersed in the deposition solution. The thickness of the liquid layer was maintained at 1 mm, and the irradiation intensity on the sample surface was 500 mM / cm 2 , and irradiation for 10 min. Photochemical deposition was performed 8 times by changing the deposition solution.

[0028] Scanning electron microscopy shows that after 8 depositions, a large amount of Cu is deposited on the surface of the W particles, forming a shell-like structure that completely blocks the W layer below. If only two depositions are performed, such as in Example 1, Cu can only just fill the gaps between the W particles, and the two elements can still be detected in all areas, but the relative contents are different. This verifies that the thickness of the Cu layer, the relative content of tungsten and copper, and the spatial distribution can be controlled by the number of depositions ( Figure 5 ).

[0029] Embodiment 3:

[0030] Dissolve 0.3873g PEHA and 2.8432g AAm in 15.8mL water to form a mixed solution, add 1mL of 10% ammonium persulfate solution to the mixed solution, and let it stand for one day. An auxiliary solution with an amine concentration of 0.5M is obtained, named P4A. Copper sulfate, P4A, and sodium ascorbate are mixed to prepare a copper deposition solution. Among them, the concentration of copper sulfate is 20mM, the concentration of amine is 25mM, and the concentration of sodium ascorbate is 100mM. Immerse a substrate covered with a thin layer of 200nm tungsten nanoparticles in this deposition solution. The thickness of the tungsten layer is about 3μm, the thickness of the liquid layer is maintained at 1mm, and the irradiation intensity of the sample surface is 500mM / cm 2 , and irradiation for 10 min. Photochemical deposition was performed 4 times by changing the deposition solution.

[0031] The sample surface was cleaned with deionized water, and the powder was continued to be applied and the above photochemical deposition process was repeated to prepare two groups of samples, one of which contained 4 layers of W powder and the other contained 6 layers of W powder. Scanning electron microscopy showed that the total thickness of the 4-layer W powder sample was about 12μm, and the total thickness of the 6-layer W powder sample was about 17μm, indicating that the thickness of the tungsten-copper composite material can be controlled by multi-layer deposition, and the total thickness of the material increases roughly proportionally with the number of deposition times ( Figure 6 ).

[0032] Embodiment 4:

[0033] 0.3873g PEHA and 1.4216g AAm were dissolved in 17.2mL water to form a mixed solution, and 1mL of 10% ammonium persulfate solution was added to the mixed solution, and the mixture was allowed to stand for one day. An auxiliary solution with an amine concentration of 0.5M was obtained, named P2A. Copper sulfate, P2A, and sodium ascorbate were mixed to prepare a copper deposition solution. Among them, the concentration of copper sulfate was 40mM, the concentration of amine was 100mM, and the concentration of sodium ascorbate was 200mM. A substrate covered with a thin layer of 200nm tungsten nanoparticles was immersed in this deposition solution, and the thickness of the liquid layer was maintained at 400μm. A circular light field was selectively projected onto a specific area of ​​the sample by a dynamic light processing projection device equipped with a 365nm ultraviolet LED light source, and the irradiation intensity on the sample surface was 100mM / cm 2 The photochemical deposition was performed twice by replacing the deposition solution.

[0034] The sample surface was repeatedly rinsed with deionized water. The W powder particles in the un-illuminated area lacked adhesion and were washed away, while the illuminated area was left behind to form a circular tungsten-copper composite material, proving that this method can simultaneously control the macroscopic geometric structure of the obtained sample ( Figure 7 ).

[0035] Comparative Example 1:

[0036] 0.3873 g of PEHA was dissolved in 19.6 mL of water to form a mixed solution, and AAm was not added to obtain a PEHA solution with an amine concentration of 0.5 M, named POA. Copper chloride, POA, and sodium ascorbate were mixed to prepare a copper deposition solution, wherein the concentration of copper chloride was 20 mM, the concentration of amine was 60 mM, and the concentration of sodium ascorbate was 100 mM.

[0037] The substrate covered with a 200nm thin layer of tungsten nanoparticles was immersed in the deposition solution. The thickness of the liquid layer was maintained at 1mm and the irradiation intensity on the sample surface was 500mM / cm 2, 10 minutes of light exposure. Photochemical deposition was performed twice by changing the deposition solution. Optical microscopy of the sample showed that a large amount of orange granular material was produced after deposition. Electron microscopy observation showed that it was Cu polycrystalline particles grown on the surface of W powder. The above experiments show that relying solely on small molecule polyamines cannot solve the wetting problem of the tungsten-copper interface. Cu does not deposit in the gaps between W particles, but tends to grow in a phase by itself ( Figure 8 ), product density based on image analysis was <90%.

[0038] Comparative Example 2:

[0039] Dissolve 0.3873g PEHA and 0.7108g AAm in 17.9mL water to form a mixed solution, add 1mL of 10% ammonium persulfate solution to the mixed solution, and let it stand for one day. Obtain an additive solution with an amine concentration of 0.5M, named P1A. Mix copper chloride, P1A, and sodium ascorbate to prepare a copper deposition solution. Among them, the concentration of copper chloride is 20mM, the concentration of amine is 60mM, and the concentration of sodium ascorbate is 100mM.

[0040] The substrate covered with a 200nm thin layer of tungsten nanoparticles was immersed in the deposition solution. The thickness of the liquid layer was maintained at 1mm and the irradiation intensity on the sample surface was 500mM / cm 2 , 10 minutes of light exposure. Photochemical deposition was performed twice by replacing the deposition solution. Optical microscopy of the sample showed that the voids in the W powder layer were partially filled with red Cu phase after deposition. Electron microscopy observations showed that the deposition of Cu caused part of the W powder to agglomerate with it into small spheres, but plate-like Cu crystals were also observed. This indicates that when the composition of the amine-based additive is not optimal, it can only partially promote the W / Cu interface bonding, and at this time, a large amount of deposited Cu tends to form a phase by itself ( Fig. 9 ), product density based on image analysis was <90%.

Claims

1. A room temperature photochemical preparation method of a nano-tungsten copper composite material, characterized in that: The steps include: (1) preparing a copper deposition solution: mixing a copper salt, an amine-containing auxiliary agent, and sodium ascorbate to prepare a copper deposition solution; wherein the copper salt is copper chloride or copper sulfate, and its concentration ranges from 10 mM to 60 mM; the concentration of sodium ascorbate is from 50 mM to 200 mM; and after the amine-containing auxiliary agent is added, the amine concentration is controlled to be between 25 mM and 140 mM; The above-mentioned amine-containing auxiliary agent is prepared according to the following method: pentaethylenehexamine PEHA and acrylamide AAm are dissolved in water to form a mixed solution, wherein the molar ratio of PEHA to AAm is controlled between 1:12 and 1:24, and the concentration of PEHA is not less than 100mM; 10% by mass of ammonium persulfate or potassium persulfate solution is added to the mixed solution; the volume of the ammonium persulfate or potassium persulfate solution is 5-10% of the mixed solution; and the mixed solution is allowed to stand for one day to allow the polymerization reaction to fully occur in the mixed solution; (2) Deposition preparation: Spread the nano-tungsten powder evenly on the substrate into a thin layer with a thickness not exceeding 10 μm; add the copper deposition liquid to the substrate, the copper deposition liquid should cover the nano-tungsten powder, and the thickness from the deposition liquid surface to the substrate surface should be at least 400 μm; (3) Photochemical deposition: Use a 365nm ultraviolet light source to vertically irradiate the deposition liquid and tungsten powder layer, and the light source intensity is not less than 100mM / cm 2 Continuous irradiation for 5-20 minutes allows the Cu ions in the deposition solution to be fully reduced and deposited in the gaps between the W powders to form a nano-tungsten-copper composite material.

2. The room temperature photochemical preparation method of a nano-tungsten copper composite material according to claim 1, characterized in that: When a large amount of Cu needs to be deposited, the deposition liquid is replaced after one deposition and multiple depositions are performed.

3. The room temperature photochemical preparation method of a nano-tungsten copper composite material according to claim 1, characterized in that: In the case where a thicker WCu composite material is required, the sample is cleaned with deionized water after Cu deposition and then coated with a layer of W powder; the photochemical deposition and cleaning and powder coating operations are repeated until the target thickness is obtained.

4. The room temperature photochemical preparation method of a nano-tungsten copper composite material according to claim 1, characterized in that: By focusing ultraviolet light onto a specific position of the tungsten powder layer through a projection device, copper can be selectively deposited there; no reaction occurs in the surrounding areas not illuminated; after the deposition is completed, the tungsten powder layer is rinsed with deionized water to wash away the unreacted part, leaving only a nano-tungsten-copper composite material with copper deposited in a specific area; thus, a nano-tungsten-copper composite material of a certain shape is prepared.

Citation Information

Patent Citations

  • Method of manufacturing ultrafine molybdenum powder or ultrafine tungsten powder surface clad metal copper

    CN101428345A

  • Preparation method of copper modified violet tungsten oxide photocatalyst

    CN104785275A

  • Method for making cadmium sulfide film or zinc sulfide film through ultraviolet light chemical water-bath deposition technology

    CN104846352A

  • Low-temperature preparation method of pure nano W-Cu composite powder

    CN107983963A

  • Preparation method of nano tungsten copper powder with core-shell structure

    CN109128143A